2019
DOI: 10.1111/ejh.13188
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of domatinostat (4SC‐202), a class I histone deacetylase inhibitor in patients with advanced hematological malignancies

Abstract: Objectives Domatinostat (4SC‐202) is a selective class I histone deacetylase inhibitor (HDACi). This phase I study investigated safety, tolerability, pharmacokinetics (PK), pharmacodynamics, and antitumor activity in patients with advanced hematological malignancies. Methods Domatinostat was administered orally once (QD) or twice daily (BID) on days 1‐14 with 7 days off or continuously days 1‐21 in a 3 + 3 design at 7 dose levels from 25 to 400 mg total daily dose (TDD). Twenty‐four patients were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Domatinostat is highly specific for HDAC 1-3 with inhibitory constant (Ki) values in the nM range. It is also an inhibitor for the histone demethylase LSD1, which is demonstrated to be a regulator of a wide spectrum of biological processes, involved in cancer development and progression (von Tresckow et al, 2019). Concomitant targeting of HDAC and LSD1 proved to be a promising strategy for the cancer treatment as it induces apoptosis by shifting the J o u r n a l P r e -p r o o f balance of anti-and pro-apoptotic BCL-2 family proteins (Haydn et al, 2017).…”
Section: Increased Expression Of Apm Genes and Mhc Class I Surface Momentioning
confidence: 99%
See 2 more Smart Citations
“…Domatinostat is highly specific for HDAC 1-3 with inhibitory constant (Ki) values in the nM range. It is also an inhibitor for the histone demethylase LSD1, which is demonstrated to be a regulator of a wide spectrum of biological processes, involved in cancer development and progression (von Tresckow et al, 2019). Concomitant targeting of HDAC and LSD1 proved to be a promising strategy for the cancer treatment as it induces apoptosis by shifting the J o u r n a l P r e -p r o o f balance of anti-and pro-apoptotic BCL-2 family proteins (Haydn et al, 2017).…”
Section: Increased Expression Of Apm Genes and Mhc Class I Surface Momentioning
confidence: 99%
“…Concomitant targeting of HDAC and LSD1 proved to be a promising strategy for the cancer treatment as it induces apoptosis by shifting the J o u r n a l P r e -p r o o f balance of anti-and pro-apoptotic BCL-2 family proteins (Haydn et al, 2017). However, the dual inhibitory activity of domatinostat has not been scrutinized yet and requires additional experiments (von Tresckow et al, 2019).…”
Section: Increased Expression Of Apm Genes and Mhc Class I Surface Momentioning
confidence: 99%
See 1 more Smart Citation
“…Signs of anticancer activity were observed, including one patient with a complete response, one patient with a partial response and 18 patients with disease stabilization as the best overall response. Domatinostat was well tolerated, showing an acceptable safety profile [22].…”
Section: Introductionmentioning
confidence: 96%
“…4SC‐202 is a novel selective class I histone deacetylase inhibitor. In vitro, 4SC‐202 was found to inhibit survival and proliferation of several type of cancer cells including hepatocellular carcinoma cell, colorectal cancer cell, medulloblastoma cell, and urothelial carcinoma cell; and phase I clinical trials for the treatment of hematological malignant tumor revealed that 4SC‐202 is safe, well tolerated with signs of antitumor activity . Thus, 4SC‐202 seems to be a promising treatment strategy for oral cancer.…”
Section: Introductionmentioning
confidence: 99%